THE HEART OF THE WOMAN (Drawings on the work of Jamila Shaʹdrach, Meʹshach and A·bedʹne·go) - Rushana Zaripova (Peerian Journals Publishing, 2024)
In the article "A Woman's Heart" written in the style of sketches dedicated to the work of Jamila Ergasheva, the writer's story "Pain" is thoroughly analyzed. It contains the thoughts that have sprung from the thinking well of a young, inquisitive literary scholar. During the analysis process, special attention is paid primarily to the author's artistic style and language.
Keywords: story; image; character; style